Pirfenidone Improves Familial Idiopathic Pulmonary Fibrosis without Affecting Serum Periostin Levels - Yasuhiko Koga; Yoshimasa Hachisu; Hiroaki Tsurumaki; Masakiyo Yatomi; Kyoichi Kaira; Shoichiro Ohta; Junya Ono; Kenji Izuhara; Kunio Dobashi; Takeshi Hisada (Medicina, 2019)
Background: Antifibrotic agents have been approved for the treatment of idiopathic pulmonary fibrosis (IPF). However, the efficacy of these drugs in the treatment of familial IPF (FIPF) has not been previously reported. Case presentation: We report the case of a 77-year-old man with FIPF, successfully treated with pirfenidone. His uncle died due to IPF, and his niece was diagnosed with the disease. He had worsening dyspnea two months prior to admission to our hospital. Upon admission, he had desaturation when exercising and broad interstitial pneumonia. Administration of pirfenidone improved his dyspnea, desaturation, and the reticular shadow on his chest radiograph. Increased fibrotic marker levels KL-6 and SP-D were also normalized in six months; treatment had no effect on his serum periostin level. Pirfenidone has been effective for over two years. Conclusion: Antifibrotic agents such as pirfenidone may be useful for the management of FIPF, as well as cases of sporadic IPF.